2018
DOI: 10.1111/2041-210x.13100
|View full text |Cite
|
Sign up to set email alerts
|

TheEGA+GNMframework: An integrative approach to modelling behavioural syndromes

Abstract: Behavioural syndromes refer to correlated suites of behavioural traits exhibiting consistent among‐individual variation, i.e. personality. Factor analysis (FA) is currently the dominant method for modelling behavioural syndromes in humans and animals. Although FA is useful for inferring the latent causes underlying trait correlations, it does not account for the pairwise behavioural interactions that also contribute to syndrome structure. Given that latent factors and pairwise interactions are likely ubiquitou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 93 publications
(210 reference statements)
0
16
0
Order By: Relevance
“…Unfortunately, using PCA to summarize the major axes of variation in these correlation matrices does not allow assessments of how well such multivariate data fit specific alternative biological hypotheses. A more suitable statistical tool in this case is structural equation modelling (SEM) (Grace, 2006) or similar multivariate methods such as factor analysis or path analysis (Martin et al., 2019), because particular a priori hypotheses for specific covariance structures (e.g., based on the available literature) can then be tested and formally compared to find the most likely fit (Dingemanse, Dochtermann, & Wright, 2010; Dochtermann & Jenkins, 2007).…”
Section: Statistical Analyses and Reporting Resultsmentioning
confidence: 99%
“…Unfortunately, using PCA to summarize the major axes of variation in these correlation matrices does not allow assessments of how well such multivariate data fit specific alternative biological hypotheses. A more suitable statistical tool in this case is structural equation modelling (SEM) (Grace, 2006) or similar multivariate methods such as factor analysis or path analysis (Martin et al., 2019), because particular a priori hypotheses for specific covariance structures (e.g., based on the available literature) can then be tested and formally compared to find the most likely fit (Dingemanse, Dochtermann, & Wright, 2010; Dochtermann & Jenkins, 2007).…”
Section: Statistical Analyses and Reporting Resultsmentioning
confidence: 99%
“…Common marmosets ( Callithrix jacchus ) are highly social cooperatively breeding New World primates that live in cohesive family groups in a variety of different habitats, from the Atlantic rain forest to the semiarid area of shrub forests (Garber et al, 2019) and have been studied in a variety of socio‐cognitive questions (Schiel & Souto, 2017). In recent years, these monkeys have become the focus of personality studies under lab conditions: they display consistent interindividual differences when assessed in a battery of experiments (Díaz et al, 2020; Koski & Burkart, 2015; Šlipogor et al, 2016; Tomassetti et al, 2019), observations (Martin et al, 2019; Masilkova et al, 2020; Šlipogor et al, 2020), questionnaires (Inoue‐Murayama et al, 2018; Koski et al, 2017; Weiss et al, 2020), and by using a combination of several different personality assessment methods (Iwanicki & Lehmann, 2015; Šlipogor et al, 2020). However, little is known about long‐term consistency of their personality structure, and no study to this date assessed the personality of wild common marmoset populations.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also been examining the extent to which common marmoset personality resembles and differs from that of other species. As in other species, behavioral experiments have revealed the presence of stable traits in common marmosets (10,11).…”
Section: Marmosets (Callithrix Jacchus)mentioning
confidence: 64%
“…Studies of common marmosets have revealed the presence of stable personality traits [10, 11], although one study found that these traits can be modified via social facilitation or social group effects [12]. Studies have also found that personality traits in common marmosets are heritable and related to well-being [13], associated with the strength of laterality [14], and the binding potential of serotonin transporters in the brain [15].…”
Section: Introductionmentioning
confidence: 99%